2019
DOI: 10.3390/ijms20235910
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Salt-Sensitive and Tolerant Genotypes Reveals Salt-Tolerance Metabolic Pathways in Sugar Beet

Abstract: Soil salinization is a common environmental problem that seriously affects the yield and quality of crops. Sugar beet (Beta vulgaris L.), one of the main sugar crops in the world, shows a strong tolerance to salt stress. To decipher the molecular mechanism of sugar beet under salt stress, we conducted transcriptomic analyses of two contrasting sugar beet genotypes. To the best of our knowledge, this is the first comparison of salt-response transcriptomes in sugar beet with contrasting genotypes. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…A previous study showed that the AA metabolism of barley is enhanced during salt stress, and the accumulation of small-molecule AAs helps to improve salt tolerance by improving osmotic regulation and by maintaining cell membrane stability [51]. Under 280 mmol/L NaCl treatment, the content of proline and free amino acids was higher in salt-tolerant variety T710MU than in saltsensitive S710 [52]. Our experimental results show that the AA metabolism of sugar beet was significantly Fig.…”
Section: Aas Are Correlated With Salt Stresssupporting
confidence: 47%
“…A previous study showed that the AA metabolism of barley is enhanced during salt stress, and the accumulation of small-molecule AAs helps to improve salt tolerance by improving osmotic regulation and by maintaining cell membrane stability [51]. Under 280 mmol/L NaCl treatment, the content of proline and free amino acids was higher in salt-tolerant variety T710MU than in saltsensitive S710 [52]. Our experimental results show that the AA metabolism of sugar beet was significantly Fig.…”
Section: Aas Are Correlated With Salt Stresssupporting
confidence: 47%
“…Being relatively salt-tolerant, the germination rate was significantly higher for lk573 than lk621 under 200 mM NaCl stress ( Figure 1K). As effective strategies, transcriptomic and proteomic analyses were widely used in revealing the molecular mechanism, responding to abiotic stresses [31,32]. To further reveal the molecular mechanism in response to salt stress and to obtain a novel understanding of salt tolerance during seed germination, an integrated analysis of transcriptomic and proteomic levels in lk573 and lk621 was conducted using RNA-seq and iTRAQ technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall is important for protecting plants from biotic stress, and its critical role in abiotic stress is widely discussed [18,31]. The UDP-glucose 4-epimerase (UGE) plays an important role in galactose metabolism and the biosynthesis of galactose-containing polysaccharides and can also participate in arabinose metabolism, affecting cell wall resistance [41,42].…”
Section: Cell Wall In Salt Tolerancementioning
confidence: 99%
“…To counter the detrimental effects of salt-induced stress, plants produce compatible solutes like free amino acids to minimize high salinity-caused osmotic stress. Positive correlations between increased salt tolerance and accumulations of total free amino acids have been reported in several crops [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%